Education and training of teacher librarians in sri langka / Padmasiri Thenabadu - Padmasiri, Thenabadu (2002)
This study was designed to find out the current status of Sri Lankan teacher librarian's training and education. A random sample of 108 respondents comprising teacher librarians, principals, and education officers was selected for this survey. Questionnaires were sent to these schools by mail. A total of 63 (68.04%) questionnaires were returned on due date. The data obtained was examined to assess the teacher librarian's training programmes and drawbacks of these programmes. Based on the findings, most of the respondents indicated that they were not satisfied with available training programmes. It was found that most of the teacher librarians are limited to very few library activities and focused to classroom teaching. They are not well trained in the library works. They do not have enough training facilities such as school library activities, computer based activities, Internet and based activities, and use of technological equipments. Most of the drawbacks were identified by the survey. The requirements of the training of teacher librarians are also revealed by the study. The main problem faced by the teacher librarians is lack of training opportunities in island wide. This resulted in limited knowledge of the profession. Therefore they are limited to perform only a few activities at their school libraries. It was also noted that most of the teacher librarians in Sri Lanka are not trained in library science. Although most of them are interested in doing school library work, they do not get the necessary training. The school libraries in Sri Lankan school need much improvement to keep pace with the current development taking shape in information technology. Based on the findings, recommendations are proposed to design the training programmes for the teacher librarians in Sri Lanka.